Functionalisations at activated and non-activated C-H bonds - Ambrosio, Teresina (2021)
Site-selective, late-stage functionalisation of non-activated C-H bonds represents a challenge for organic chemists because these bonds are among the strongest in nature. Particularly, with regards to chlorination of non-activated C-H bonds, a method that allows for their benign, facile ad site-selective chlorination has yet to be developed.